Ectopic gene conversion in prokaryotic and yeast genomes - Morris, Robert T (University of Ottawa (Canada), 2007)
The repair of double strand DNA breaks is important to genomic stability. Gene conversions are non-reciprocal exchanges of DNA created through the repair of double strand DNA breaks. Relatively few studies have looked at examining the similarities and differences of the physical characteristics of ectopic gene conversions (conversions between non-allelic genes) within and between diverse lineages of prokaryotes and yeast. I found that several factors affect the frequency of ectopic gene conversions in prokaryotes and yeast. The size and organization of multigene families affects how often genes are converted. In E. coli a positive correlation was found between gene family size and conversion frequency. In yeast, I found that intra-chromosomal gene conversions are more frequent than inter-chromosomal conversions. The amount of sequence similarity between the converted genes affects their conversion frequency. I found that long conversions tend to occur between highly similar homologs. In addition, the sequence similarity requirements are not uniform for every organism. For example, I found indications that the life-style of the organism affects the stringency of sequence similarity requirements for ectopic gene conversion. I determined that ectopic gene conversions occur more frequently and require significantly less flanking similarity in the pathogenic bacteria strains than in the non-pathogenic. The functional importance of the converted genes affects how frequently they are converted. Genes that have been functionally maintained throughout evolution are ectopically converted less frequently than genome specific paralogs. Nucleotide distance between homologous genes affects their ectopic conversion frequency. In paralogous multigene families of yeast, gene conversions occur more frequently between genes which are close together on the same chromosome than between dispersed homologs. Converted regions are not uniformly distributed along the length of genes. Converted regions tend to be clustered near the 3' end of genes in yeast but not in prokaryotes. I also looked at the effects of gene conversions on nucleotide composition of yeast genes and found that repeated ectopic gene conversions between dispersed homologs tend to increase the converted genes GC-content.
Keywords: Biology, Molecular.